2017
DOI: 10.1039/c7tb00030h
|View full text |Cite
|
Sign up to set email alerts
|

pH/redox dual stimuli-responsive sheddable nanodaisies for efficient intracellular tumour-triggered drug delivery

Abstract: p(His)-S-S-polyurethane-S-S-p(His) triblock copolymer nanodaisies exhibit efficient pH and glutathione responsive doxorubicin releasing behaviours under physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…1 ). Generally, pH-responsive nanoparticles are fabricated either using acid-sensitive linkers or ionizable groups [ 30 ].
Fig.
…”
Section: Targeting Of Common Attributes Of Tmementioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Generally, pH-responsive nanoparticles are fabricated either using acid-sensitive linkers or ionizable groups [ 30 ].
Fig.
…”
Section: Targeting Of Common Attributes Of Tmementioning
confidence: 99%
“…The pH-dependent property of pHis is due to the presence of lone-pair electrons on the unsaturated nitrogen in the imidazole group of pHis. Our group previously reported a variety of pHis-based polymeric micelles for the delivery of doxorubicin (DOX) [ 30 33 ]. Poly (ethylene glycol) methyl ether acrylate-block poly(L-lysine)-block-poly(L-histidine) triblock co-polypeptides were synthesized for pH-responsive drug delivery.…”
Section: Targeting Of Common Attributes Of Tmementioning
confidence: 99%
“…Therefore, poly(Histidine) (pHis) has been extensively used for the fabrication of pH-sensitive drug delivery nanosystems. Uthaman and his team (2018) have reported a variety of pHis-based polymeric micelles for the delivery of DOX [15,29,[46][47][48]. In addition to these, nanocarriers composed of amphiphilic, biocompatible chitosan polymeric micelles were used to deliver Nonsteroidal anti-inflammatory drug (NSAID) Ibuprofen in breast cancer therapy.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…Generally, pH-responsive nanoparticles are fabricated either using acid-sensitive linkers or ionizable groups [15]. A variety of pHsensitive nanoparticles have been designed in recent decades and have characteristic functionalities in the molecular structure, where pK a (negative logarithm of the acid dissociation constant) values are close to the tumor interstitial pH.…”
Section: Introductionmentioning
confidence: 99%
“…Further DOX release could be triggered by low pH or by treatment with 10 mM of GSH, and fluorescence indicated that the nanomicelles could be biodistributed in the animal model within 72 hours and inhibit CT26 tumors. 130 Reduction-and pH-responsive nanomicelles, composed of poly(styrene-alt-maleic anhydride) and short PEG chains, were used for delivering drugs and PLK-1 siRNA. These micelles were coated with BSA to enhance their stability.…”
Section: Multiple Functional Sensitive Nanomicellesmentioning
confidence: 99%